A Case of an Undifferentiated Squamous Cell Carcinoma Arising from an Epidermal Cyst - Mai Tokunaga; Masami Toya; Yuichiro Endo; Akihiro Fujisawa; Miki Tanioka; Mayumi Kato; Yoshiki Miyachi (Case Reports in Dermatological Medicine)
An epidermal cyst is a common benign subcutaneous tumor and rarely develops malignancy. We report a case of an undifferentiated cutaneous squamous cell carcinoma (SCC) that arose from an epidermal cyst on the left side of the neck. The epidermal cyst had rapidly increased in size and presented cauliflower-like tumor. Histological study revealed undifferentiated squamous cell carcinoma that was arising from the epidermal cyst.